Training and fatigue in competitive swimming: Coaches perceptions - Thow, J.; Turner, A. P.; Nash, C.; Sanders, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The performance of swimmers is often limited by fatigue; a complex, multi-factorial phenomenon (Alberty et al., 2009). However, little is known about coaches` understanding of fatigue, nor how they currently manage it during training in swimming. The purpose of this study was to examine coaches` current practices and knowledge about fatigue during training in competitive swimming. Methods: A questionnaire was sent to 374 UK based coaches, currently coaching national age-group swimmers, using the Bristol Online Survey website. The questionnaire was separated into 5 sections: demographic information; causes and effects of fatigue (Ament and Verkele, 2009); methods of monitoring fatigue; the management and prevention of fatigue; additional information. Open and closed questions ad 7-Point Likert-scales were used throughout the questionnaire (Portney and Watkins, 2000). Results: Out of the 100 respondents, 79% monitored the state of fatigue of their athletes during a training session. Coaches were most familiar with a `psychological decrease in motivation, interest or enthusiasm` as a mechanism (25%) and effect (32%) of fatigue. The main method used to monitor fatigue was the personal visual observation of technique. Significant associations were found from the Chi square test (p value) between the key variables of coaching qualification and years of experience; the equipment used to monitor fatigue during training, including; underwater video (p=13.081, 14.496 respectively), above water video (p=16.975), sleep quantity/quality (p=9.512), body mass (p=14.534) and hydration level (p=9.646); and blood lactate levels (p=18.530). No significant associations were found between the key variables and coaches` knowledge and fatigue mechanisms and effects. 98% of the respondents made changes to their session plan to enable swimmers to cope with the training intensity. Discussion: This study identified that coaches place a high importance on the effect and management of fatigue during training in competitive swimmers. Their methods of monitoring fatigue during training are linked to coaching experience and qualifications in swimming. More research is needed to ensure current coaching practices and courses are effective to enable swimmers to cope with the high physical and mental demands of training in swimming.